IDENTIFIKASI KEPUASAN KONSUMEN DITINJAU DARI SEGI HARGA DAN KUALITAS PADA RESTORAN ABUBA STEAK DI GREENVILLE - Tommy Setiawan Ruslim; Mukti Rahardjo (Jurnal Ilmiah Manajemen dan Bisnis, 2016)
At the time of the current era of globalization, every company should be able to compete with competitorsin order to survive. The most striking is the intense competition in the food industry, the number ofcompetitors and substitute products, Is very vulnerable to those who engaged in it to be able to compete if they can not satisfy customers. To that end, the authors are interested in creating a research against one ofthe restaurants there, by taking Abuba steak at Greenville as research material, with price as theindependent variable (X1) and quality service as the independent variable (X) to satisfaction as thedependent variable (Y). This research is done by spreading the questionnaire to 100 respondents. Throughthe data processing with PASW 18.00 is known that price as independent variable (X2) and service quality(X2), but only service quality (X21) have a significant effect on customer satisfaction (Y). Note that for 0.472for satisfaction variation can be explained by the variable price and service quality of 0.283 while the restcan be explained by other variables. With the linear regression equation is Y = 9.251 - 0.084 (X) + 0.450(X).